Pengaruh Komposisi Media Arang Sekam pada Pembibitan Cabai Hiyung Menggunakan Batang Pisang - Akhmad Gazali; Riza Adrianoor Saputra; Dwi Jaka Ananda (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2022)
Hiyung is officially registered at Center for Plant Varieties Protection and Agricultural Licensing, Ministry of Agriculture Republic of Indonesia No. 09/PLV/2012 at April 12, 2012. Rice husk charcoal as an addition to the growing media is also often proven to increase crop yields. Banana stems are generally used as liquid fertilizer, furthermore banana stems contain several mineral such as Fe, Na, Mg which are needed by plants. This research aims to determine the effect of rice husk charcoal planting media composition on the growth of Hiyung seedlings and to find out the best growing media composition in increasing the growth of Hiyung seedlings on banana stems. This research was conducted in May-July 2021 at the Greenhouse and Integrated Laboratory of the Department of Agroecotechnology, and the Soil Laboratory of the Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, South Kalimantan. The research method used was a single factor randomized block design with p1 (100g soil), p2 (50g soil + 50g rice husk charcoal), and p3 (100g rice husk charcoal) treatments. The results showed that the treatment of 100g rice husk charcoal was able to increase the percentage of plant life, seedling height, number of leaves, and root length of Hiyung seeds on banana stems.